2006
DOI: 10.4049/jimmunol.177.2.1349
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR9 in Anti-Nucleosome and Anti-DNA Antibody Production in lpr Mutation-Induced Murine Lupus

Abstract: Systemic lupus erythematosus is characterized by the production of autoantibodies directed against nuclear Ags, including nucleosome and DNA. TLR9 is thought to play a role in the production of these autoantibodies through the capacity of nuclear immunogenic particles to interact both with BCR and TLR9. To determine the role of TLR9 in SLE, C57BL/6-lpr/lpr-TLR9−/− and TLR9+/+ mice were analyzed. The abrogation of TLR9 totally impaired the production of anti-nucleosome Abs, whereas no difference was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 45 publications
10
101
3
3
Order By: Relevance
“…Treatment of mice with CpG to stimulate TLR9 has alleviated disease severity in colitis, arthritis, and diabetes (50)(51)(52)(53). In addition, lupus-related renal disease is exacerbated in TLR9-deficient autoimmune prone mice (20)(21)(22)(23), and recent reports suggest that TLR9 is required to prevent pathological responses that result from TLR7-mediated signaling (24,25). Other studies, however, show that TLR9 stimulation has an adjuvant effect driving Th1 responses allied with IgG2a antibodies, thereby potentially exacerbating autoimmune disease (19,(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment of mice with CpG to stimulate TLR9 has alleviated disease severity in colitis, arthritis, and diabetes (50)(51)(52)(53). In addition, lupus-related renal disease is exacerbated in TLR9-deficient autoimmune prone mice (20)(21)(22)(23), and recent reports suggest that TLR9 is required to prevent pathological responses that result from TLR7-mediated signaling (24,25). Other studies, however, show that TLR9 stimulation has an adjuvant effect driving Th1 responses allied with IgG2a antibodies, thereby potentially exacerbating autoimmune disease (19,(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 97%
“…The BCR can deliver chromatin complexes from the AC to the endosome, allowing Toll-like receptor 9 (TLR9)-mediated signaling (18,19). Despite this, lupus-related renal disease is exacerbated in TLR9-deficient mice (20)(21)(22)(23), suggesting a regulatory role for TLR9-induced activation of self-reactive B cells in health that breaks down when tolerance is lost, leading to autoimmunity (24,25).…”
mentioning
confidence: 99%
“…Indeed, the reactivity of sera from B6 lpr/lpr -Tlr4-deficient mice was strongly decreased against both Gram-positive and Gram-negative bacterial extracts. Thus, the absence of a second signal may explain, on the one hand, the decreased production of anti-DNA and anti-CL Abs and, on the other hand, the unchanged anti-nucleosome autoantibody response considered to be dependent on either the presence of T cell clones specific for nucleosome (42) or TLR9 signaling (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In lupus, several reports have focused on the role of TLRs which recognize nucleic acids including TLR3, 7, and 9 (19,20) and demonstrated that their engagement participates in the induction of antinuclear autoantibodies. Recently, using the C57BL/6 lpr/lpr model, we demonstrated that TLR9 is basically required for production of anti-nucleosome Abs (21). Significantly, TLR9-deficient mice presented a more severe disease, suggesting that TLR9 engagement may have a protective role, possibly through the induction of autoantibodies participating in the clearance of apoptotic cell products known to initiate and propagate the disease (20).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…In MRL-Fas lpr mice, lack of TLR9 had different effects on anti-nuclear Ab specificity in different studies, yet overall disease was inexplicably exacerbated (10)(11)(12). TLR9-deficiency also enhanced disease in MRLFas wt (11), B6-Fas lpr (13), and mutant Plcg2 ϩ/Ali5 mice (14). In striking contrast, lupus-prone Fc␥RIIB Ϫ/Ϫ mice expressing a high-affinity anti-DNA transgene had reduced disease (15), although this may be related to dependence on a single transgenic anti-DNA specificity.…”
mentioning
confidence: 99%